Detection of poliovirus infection in children with acute gastroenteritis in Chiang Mai, Thailand - Kattareeya Kumthip (2018)
© 2016 Wiley Periodicals, Inc. Poliovirus (PV) is typically transmitted by the fecal-oral route, which means that the risk of infection and virus distribution could be achieved by exposure to the virus contaminated in food and water. The aim of this study was to determine the occurrence of PV strains by detecting the virus in pediatric patients who admitted to the hospitals with diarrhea in Chiang Mai, Thailand during 2010–2015. By applying a reverse transcription-polymerase chain reaction and nucleotide sequencing analysis of 1,300 stool specimens collected from pediatric patients, PVs were detected at 0.61% (8 out of 1,300 specimens). Among eight PV positive samples, mixed infection with norovirus or human bocavirus was detected in one each out of eight cases. All PV strains detected in this study were characterized further by phylogenetic analysis of 343 bp of the 5′ UTR and 315 bp of the partial VP1 sequences. The results revealed that eight PV strains detected in the present study two of each were PV1 and PV2, and four were PV3 serotypes of the Sabin vaccine strains. The data demonstrated the presence of PV1, PV2, and PV3 Sabin vaccine strains in children with acute gastroenteritis in Chiang Mai, Thailand. J. Med. Virol. 89:775–781, 2017. © 2016 Wiley Periodicals, Inc.